Vietnam POWs Stories of survival - Leonard, Brian; MacDonald, Terry; Harvey, Mike; Knight, Graham; Burns, Steve (Discovery Communications, Inc., 1999)
Marking the 25th anniversary of the return of American POWs from Vietnam, this program shows the remarkable determination and human spirit of men (and possibly women) who refused to die. People whose only thoughts were to survive and return home. The POWs held in SouthEast Asia during the Vietnam conflict tell their own stories. The first Americans were taken into custody in the spring of 1962 while in charge of a South Vietnamese training exercise. The last of 725 accounted for POWs came back to the US on April 1, 1973. This film presents life in the camps called "The Zoo", "The Briarpatch", "Alcatraz", and others, and what was happening in the US to try to get the prisoners out